Taxing Billionaires: Estate Taxes and the Geographical Location of the Ultra-Wealthy - Enrico Moretti; Daniel Wilson (Institute of Labor Economics (IZA), 2019)
We study the effect of state-level estate taxes on the geographical location of the Forbes 400 richest Americans and its implications for tax policy. We use a change in federal tax law to identify the tax sensitivity of the ultra-wealthy's locational choices. Before 2001, some states had an estate tax and others didn't, but the tax liability for the ultra-wealthy was independent of their domicile state due to a federal credit. In 2001, the credit was phased out and the estate tax liability for the ultra-wealthy suddenly became highly dependent on domicile state. We find the number of Forbes 400 individuals in estate tax states fell by 35% after 2001 compared to non-estate tax states. We also find that billionaire's sensitivity to the estate tax increases significantly with age. Overall, billionaires' geographical location appears to be highly sensitive to state estate taxes. We then estimate the effect of billionaire deaths on state tax revenues. We find a sharp increase in tax revenues in the three years after a Forbes billionaire death, totaling 165 million for the average billionaire. In the last part of the paper, we study the implications of our findings for state tax policy. We estimate the revenue costs and benefits for each state of having an estate tax. The benefit is the one-time tax revenue gain when a wealthy resident dies, while the cost is the foregone income tax revenues over the remaining lifetime of those who relocate. Surprisingly, despite the high estimated tax mobility, we find that the benefit exceeds the cost for the vast majority of states.
Keywords: J01; R10; H10; 330; Forbes 400; Geographical mobility